The Structural Difference of Isobaric N-Glycans of Two Microalgae Samples Reveals Taxonomic Distance - Mócsai, Réka; Kaehlig, Hanspeter; Blaukopf, Markus; Stadlmann, Johannes; Kosma, Paul; Altmann, Friedrich (Frontiers in Plant Science, 2021)
Microalgae of the Chlorella clade are extensively investigated as an environmentally friendly source of renewable biofuels and high-value nutrients. In addition, essentially unprocessed Chlorella serves as wholesome food additive. A recent study on 80 commercial Chlorella preparations revealed an unexpected variety of protein-linked N-glycan patterns with unprecedented structural features, such as the occurrence of arabinose. Two groups of products exhibited a characteristic major N-glycan isobaric to the Man2GlcNAc2XylFuc N-glycan known from pineapple stem bromelain, but tandem mass spectrometry (MS/MS) analysis pointed at two types of N-glycan different from the bromelain structure, as well as from each other. Here we report the exact structures of these two novel N-glycan structures, elucidated by nuclear magnetic resonance spectroscopy and MS/MS, as well as on their phylogenetic context. Despite their humble size, these two N-glycans exhibited a very different design with structural features unrelated to those recently described for other Chlorella-clade strains. The major glycans of this study presented several novel structural features such as substitution by arabinose or xylose of the internal N-acetylglucosamine, as well as methylated sugars. ITS1-5.8S-ITS2 rDNA barcode analyses revealed that the xylose-containing structure derived from a product primarily comprising Scenedesmus species, and the arabinose-containing glycan type related to Chlorella species (SAG211-34 and FACHB-31) and to Auxenochlorella. This is another example where characteristic N-glycan structures distinguish phylogenetically different groups of microalgae.